Pola Asuh Orang Tua Dan Perkembangan Sosial Anak - Siti Masyithoh (At-Tajdid: Jurnal Ilmu Tarbiyah, 2018)
Parents’ parenting is one of the important variables that can affect the development of all potential learners including social development. The importance of parents’ parenting in the process of social development of children will be described in this paper. The paper is presented in the form of narrative descriptive analysis by presenting expert opinions and research results related to parenting patterns and social development of children, which aims to provide a clear understanding related to parenting patterns and the development of social skills of children so that it can inspiring educators and parents to choose and apply proper parenting in the educational process.